The eudemian ethics on the voluntary, friendship, and luck : the Sixth S.V. Keeling Colloquium in Ancient Philosophy - Leigh, Fiona. (Philosophia Antiqua, 2012)
Reflecting the relatively recent high level of scholarly interest in Aristotle's Eudemian Ethics (EE), each paper in this collection is concerned first and foremost to understand the arguments from the EE it examines in terms of that work alone. The papers, by David Charles, Christopher Rowe, M.M. McCabe, Jennifer Whiting, and Friedemann Buddensiek, focus variously on the topics of the voluntary, friendship and luck, only drawing on other texts in the service of illuminating the EE. The result is a volume containing novel, at times even conflicting, readings of questions central to understanding this important text and Aristotle's ethics in general. \'...each of the five essays targets an important but relatively circumscribed issue, and together they should convince anyone of the desirability of fresh and serious investigation of the Eudemian Ethics.\' Daniel P. Maher, Assumption College